Adverse drug events of immune checkpoint inhibitors - a retrospective, descriptive real-world data analysis - Lauris Annatha Mariam Auch; Chloé Sieber; Dirk Lehnick; Balthasar L. Hug (BMC Cancer)
Abstract Aims The objective of this study was to analyze immune-related adverse events (irAEs) in a real-world data sample and examine the differences in incidence between affected organ systems, irAE severity, therapeutic agent, and gender. Methods We retrospectively analyzed all consecutive patients treated with anti-cytotoxic T-lymphocyte associated protein 4 (CTLA-4) antibodies, anti-programmed death 1 (PD-1) inhibitors, and programmed death-ligand 1 (PD-L1) inhibitors between January 2020 and May 2023 in a tertiary referral center in Switzerland. IrAEs documented in the electronic health records (EHR) were graded according to the Common Terminology Criteria for Adverse Events (CTCAE) and analyzed descriptively. Results Among the 500 patients, 196 (39.2%) were female. Treatments included pembrolizumab (51.2%), atezolizumab (20.2%), nivolumab (14.4%), durvalumab (6.4%), ipilimumab in combination with nivolumab (4.8%), cemiplimab (1.4%), avelumab (1.2%), and ipilimumab (0.4%). N = 216 (43.2%) patients had ≥ 1 irAEs (females: 47.4%; males: 40.5%). Severe (≥ grade 3) irAEs were reported in 13.6% of patients. The following irAE incidences were found: dermatological (15.2%), gastrointestinal (13.0%), endocrine (10.8%), musculoskeletal (4.8%), pulmonary (3.8%), systemic (3.6%), neurological (2.6%), cardiac (1.4%), renal (1.4%), hematological (0.6%), and ocular (0.2%). Conclusion Nearly half of the patients experienced ≥ 1 irAEs, of which one-third severe. Females experienced more irAEs than males, above all due to a higher incidence of grade 1 irAEs. Only about half of the irAEs were reported as coded diagnosis. Further prospective studies on irAEs are warranted using structured documentation.